Utilizamos conectores de contraste en un texto - Ramírez Adrianzen, Novar Junet (2019)
The session entitled: “We use contrast connectors in the text”, was developed in the area of communication, taking into account the competence writes various types of texts in their mother tongue, based on the necessary resources such as the capabilities adapt the text to the communicative situation, organize and develop the ideas in a coherent and cohesive way, use conventions of the written language in a relevant way and reflect and evaluate the form, content and context of the written text, it has been possible to achieve in the students the performance relates ideas through some (contrast) connectors according to the needs of the text it produces. _x000D_ In the course of the session, motivational and challenging activities were applied that encouraged children to build their capacities to understand all text that they read and produce creatively, appropriate to their respective use situations. _x000D_ The pedagogical processes such as motivation and exploration of previous knowledge, problematization, construction of learning and information processing, evaluation and transfer in the didactic processes of the area were taken into account. _x000D_ The learning strategies were consistent with the interests and needs of students in sixth grade of primary education.